Relationship Between Income and Length of Work Factors with the Incidence of Work Stress on the Bus Drivers in Pandemic Covid-19 - Tri Raharjo; Siti Musyarofah; Ainul Maghfiroh (Global Health Science Group, 2021)
Several empirical research have proven that expert drivers are a susceptible occupational group, normally uncovered to environmental stressors and detrimental running conditions. Additionally, latest studies has connected paintings-associated pressure to bad overall performance and sdestructive fitness results on this occupational group, inclusive of cardiovascular ailment and dangerous automobile operations, the painting pressure of bus drivers in 2020 has a tendency to boom withinside the COVID- 19 pandemic state of affairs, the authorities urges humans to perfom self-quarantine in order that the unfold and transmission of the corona virus outbreak will decrease. Methode used cross sectional study, The analysis used the Chi-square statistical test with the alternative using Fisher's test because the variables studied were on an ordinal scale and used extra than businesses of unpaired samples, Sampling on this study turned into executed with the aid of using easy random sampling. The researcher randomly 30 drivers. The results of bivariate analysis the use Fisher's test have been carried out to decide among income and the incidence of work stress in the bus driver, obtained p value of 0.016. The p value is much less than 0.05 (p value <0.05), and length of work obtained p vaue 0.01 it is able to be interpreted that there is a relationship between income and working periode factors with the incidence of work stress on the bus driver at Bahurekso Kendal terminal.